Comparative study of the removal of urea by electrocoagulation and electrocoagulation combined with chemical coagulation in aqueous effluents - A. Shaban; M. E. Basiouny; Osama A. AboSiada (Scientific Reports)
Abstract Urea is a major issue in human wastewater because it may be easily broken down by the urease enzyme produced by bacteria, leading to ammonia production. Due to its ability to increase soil pH and eutrophicate streams, ammonia-containing effluent emissions pose environmental and health risks. This study aimed to evaluate the effectiveness of various treatment approaches in reducing urea concentrations by comparing the removal rates of conducting electrocoagulation (EC), EC followed by chemical coagulation (EC-CC), and CC followed by electrocoagulation (EC-CC). Numerous electrocoagulation parameters have been investigated, including current density, electrode gap distance, electrolyte type, concentration, and electrolysis duration. The electrode morphology was examined using a scanning electron microscope, while the produced sludge was analyzed using Fourier transform infrared spectroscopy. Three kinds of aluminum coagulants—potash alum, aluminum sulfate, and aluminum chloride—were used in the chemical coagulation, while the electrocoagulation was optimized at 30 A/m2. The results of this investigation suggest that the application of EC-CC, regardless of the type of coagulant used in both synthetic and real effluent, could marginally improve the efficacy of urea removal. Conversely, CC-EC exhibits an adverse effect on the efficiency of urea removal in both synthetic and real wastewater. The application of CC-EC demonstrated a significant improvement in the effectiveness of COD removal from actual wastewater, according to experimental results. The study emphasized the effectiveness and economic advantages of electrocoagulation over EC-CC and CC-EC techniques, used to remove urea from both real and synthetic wastewater.